Perceived Workplace Stress Is Associated with an Increased Risk of Prostate Cancer before Age 65 - Blanc-Lapierre, Audrey; Rousseau, Marie-Claude; Parent, Marie-Elise (Frontiers in Oncology, 2017)
Background: Evidence is lacking regarding the potential role of chronic psychological stress on cancer incidence. The workplace is reported to be the main source of stress among Canadian men. We examined the association between perceived lifetime workplace stress and prostate cancer risk in a large case-control study. Methods: Cases were 1933 men, aged ≤75 years, newly diagnosed with prostate cancer in 2005-2009 across hospitals in Montreal, Canada. Concurrently, 1994 population controls frequency-matched on age were randomly selected from the electoral list based on cases’ residential districts. Detailed lifestyle and work histories (including perceived stress, from any type of work stressor, for each job held) were collected during in-person interviews. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for the association between work-related stress and prostate cancer risk in multivariate analyses. Results: Over the lifetime, 58% of subjects reported at least one job as stressful. Occupations described as stressful were most often among white-collar workers. Perceived workplace stress duration was associated with a higher risk of prostate cancer (OR=1.12, 95%CI:1.04-1.20 per 10-year increase) among men younger than 65 years, but not among older men. Associations were similar irrespective of prostate cancer aggressiveness. Frequent or recent screening for prostate cancer, age at first exposure and time since exposure to work-related stress, and socioeconomic and lifestyle factors, had little influence on risk estimates. Conclusions: Findings are in line with an association between reporting prolonged workplace stress and an increase in risk of prostate cancer before age 65.